EDITORIAL (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In the 2016 December edition of Yesterday&Today educators of history can look forward to a variety of thought-provoking and insightful research articles on history theory and critical pedagogy. The scientific research section contains topics such as the need for multi-perspectives, oral history and historiography in a history course for preservice teachers; the politics of gendering decolonisation and decolonising gender within the framework of the South African history curriculum; an analysis of the depiction of women in a Malawian history textbook; utilising the Stone Age for sport historical teaching; and a historical survey of the development of Afrocentricity. The two articles in the hands-on section refer to valuing heritage and teaching good citizenship in schools in a post-colonial, post-apartheid era, followed by possible methodological approaches in the teaching and assessment of Holocaust history and the theories of race.
Keywords: history theory; critical pedagogy; multi-perspectives; oral history; historiography; decolonisation; decolonising gender; South African history curriculum; Stone Age; sport historical teaching; Afrocentricity; Holocaust history; theories of race